Faktor-Faktor yang Mempengaruhi Kinerja Keuangan dengan Moderasi Pengungkapan CSR pada Perusahaan di Industri Pertambangan Indonesia - Sufiyati; Cassandra Lee (Masyarakat Ekonomi Syariah Bogor, 2024)
The study aims for empirical evidence about the effect of managerial ownership, institutional ownership, and leverage as independent variables on dependent variable as financial performance with a moderating variable in the form of CSR disclosure in the mining industry listed on the Indonesia Stock Exchange for 2018-2022. Managerial ownership in this study is measured by dividing the number of managers who own shares in the company by number of ordinary shares outstanding. Institutional ownership in this research is measured dividing the number of institutions that own shares in the company by number of ordinary shares outstanding. Leverage in this study is measured by the Debt to Assets Ratio (DAR) which is calculated by dividing total liabilities by total assets. CSR Disclosure in this study is measured by dividing the number of CSR disclosed by total number of CSR. Financial performance in this study is measured by the Return on Assets Ratio (ROA) which is calculated by dividing net income by total assets. The total sample for this research was 10 companies, where the sample was selected using a purposive sampling method. This research data was analyzed using multiple linear regression analysis techniques processed with SPSS 23.0. The results of this research show that institutional ownership has a significant positive influence on financial performance and CSR disclosure is able to moderate the negative influence of institutional ownership and leverage on the company's financial performance, while managerial ownership and leverage do not have a significant influence and CSR disclosure is unable to moderate the influence of managerial ownership on financial performance.